Aplicação de um framework conceitual de gestão do conhecimento para melhoria em DevOps - Pavan, Diogo Reis (2018)
DevOps (Development and Operations) is a cultural movement that aims to approximate the development team, which is responsible for new functionalities and products, and the operation team, which is responsible to implant and maintain the systems. Such culture is supported by tools and practices that make it possible the automation and agility on developing and delivering high-quality software. However, the effective adoption of DevOps is affected by: (i) lack of academic efforts to support the industrial environments; (ii) lack of knowledge management in software organizations; (iii) lack of awareness of organizations that DevOps is a cultural movement. Thus, the main goal of this study is to provide information to support the DevOps adoption in real-world scenarios of software development, by means of Knowledge Management. In addition to that, it is presented an investigation about the DevOps cultural scenario and knowledge management in the national context. Then, two empirical evaluation were conducted: (i) a case study in a practical software development scenario, exploring the DOKS framework to the evaluation and support of DevOps practices and principles with focus on the knowledge management; and (ii) applying a survey in the national context in order to identify practices, benefits, and limitations on adopting the DevOps culture. Our results have revealed: (i) the study case helped in the improvement of the DevOps scenario and the Knowledge Management in the study object; and (ii) the survey made it possible for a partialinitial evaluation of DevOps and Knowledge Management at a national level.